Inclusive Finance in Sembako Program: An Overview From Proper Governance Perspective - Habibullah; Jayaputra, Achmadi; Pudjianto, Bambang; Muhtar (Asean Social Work Journal, 2022)
The Sembako program is one of the social protection programs launched by the Government of Indonesia to overcome poverty by providing food assistance. The sembako program is also expected to increase financial inclusion by using the prosperous family card as an electronic money and savings feature. This study uses a proper governance perspective with the research location in Banyumas Regency, Central Java Province, Indonesia. The results showed that the implementation of the Sembako program went well. However, the recipients complain that  the types, quantities, and goods received are different from the instructed provisions, so they are not in accordance with the principles of proper governance. The sembako program contributes little to increasing financial inclusion because the KKS Card can only be used to take assistance from the sembako program and cannot access other banking services. It was found that the KKS Card was not held by the recipient of the basic food program, and the recipient did not memorize the KKS Card Pin. This study recommends that all shops and stalls carry out the distribution of the sembako program without being limited to certain stalls. The sembako program is not packaged so that beneficiaries are free to take basic food assistance according to the needs of their families.